A self-heating oxygen pump using microchanneled ceramic membranes for portable oxygen supply - Shao, Xin; Dong, Dehua; Parkinson, G.; Li, Chun-Zhu (Pergamon, 2018)
© 2018 A ceramic oxygen pump has been investigated as a potential self-heated oxygen generation device using electric potential as driving force. The required high temperature (around 748 °C) can be maintained locally on the membrane while the environmental temperature is kept at lower than 200 °C. The conventional dense membrane structure was found to be inappropriate for this application because it could not withstand the thermal shock induced by rapid heating and cooling. In contrast, the microchanneled membrane used in this work demonstrated excellent thermal shock resistance. It also demonstrated high Faraday efficiency when no electrode was coated on the microchannel surface. The Faraday efficiency exceeded 90% at 748 °C when 6.35 A cm-2 current density was applied. Under these conditions, an oxygen flux density of 20.6 ml cm-2 min-1 was achieved and this continued for 100 h without any degradation. Combined, these factors demonstrate that the microchanneled membrane can be potentially utilized within an oxygen generator having small size and good durability.